2013
DOI: 10.1590/s1413-81232013001000034
|View full text |Cite
|
Sign up to set email alerts
|

Dificuldades diárias associadas às próteses totais

Abstract: The effectiveness of health services can be evaluated from the quality of life (QOL) standpoint. Thus, this study evaluated rehabilitation services using full conventional dentures (FCD) of Specialized Dental Care Centers (SDCC) in Rio Grande do Norte (RN) regarding daily difficulties associated with these dentures made between 2007 and 2009. A cross-sectional study was conducted with 138 users of these FCD, collecting data by clinical examination and a questionnaire based on the Oral Impacts on Daily Performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
0
8
0
10
Order By: Relevance
“…Author/year/type of publication Machado et al (2013) Construction of secondary attention in oral health: a study about the centers of dental specialties in Pernambuco, Brazil…”
Section: Discussionmentioning
confidence: 99%
“…Author/year/type of publication Machado et al (2013) Construction of secondary attention in oral health: a study about the centers of dental specialties in Pernambuco, Brazil…”
Section: Discussionmentioning
confidence: 99%
“…But in spite of this, they still use it. This situation is also associated with tooth loss throughout life and many use inappropriate prostheses [10][11][12]. Some studies have reported that there is an adaptation to dental prostheses, regardless of their quality [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Apesar de não ter sido objeto na fase de coleta de dados nesta pesquisa a questão socioeconômica da população, isto possui estreita relação com a condição bucal 6,9,29,30 . Da população do interior da região Norte 29,1% apresenta renda familiar de até R$ 500,00 reais por mês e, 49,2% população entre R$ 501,00 até R$ 1.500,00 reais por mês 9 , valores inferiores aos vencimentos de um Cabo do Exército Brasileiro 31 .…”
Section: Introductionunclassified
“…Isto é corroborado por outras pesquisas que relataram associação de baixa renda mensal, de até três salários mínimos, e baixo nível de escolaridade como recorrente nas populações que buscam atendimento, estando relacionados à perda dentária 6,9,18,27,29,32 .…”
Section: Introductionunclassified
See 1 more Smart Citation